A case series of suprascapular nerve block (with an historical comparator) for shoulder pain in motor neurone disease. (September 2020) - Shanahan, E Michael; Glaezter, Karen; Gill, Tiffany; Hill, Catherine; Graf, Scott; Allcroft, Peter
Background: Shoulder pain is a distressing but under-reported and poorly managed symptom in people with motor neurone disease. Objectives: This study aimed to assess the efficacy of suprascapular nerve block for the management of shoulder pain in patients with motor neurone disease. Methods: A total of 27 patients with motor neurone disease and shoulder pain were offered a suprascapular nerve block. Ten of these patients had bilateral shoulder pain and both were injected, making a total of 37 shoulders. The patients were followed up for a total of 3 months, or until death. Shoulder pain was measured using the pain scale (out of 100) of the shoulder pain and disability index and compared with baseline scores and a placebo control group from an earlier study using the same methodology (ACTRN12619000353190). Results: Following the nerve block there was a significant improvement of pain scores from baseline (58.4) at week 1 (20.8, p  < 0.000), week 6 (17.6, p  < 0.000) and week 12 (30.4, p  = 0.001) and a significant improvement compared with the control group across each time interval. Conclusion: Suprascapular nerve block is a safe, effective therapy for patients with chronic shoulder pain.